1995
DOI: 10.1002/arch.940290106
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of energetic amino acid metabolism inAcyrthosiphon pisum: A multidimensional approach to amino acid metabolism in aphids

Abstract: Aphids are highly specialized insects that feed on the phloem-sap of plants, the amino acid composition of which is very unbalanced. Amino acid metabolism is thus crucial in aphids, and we describe a novel investigation method based on the use of 14C-labeled amino acids added i n an artificial diet. A metabolism cage for aphids was constructed, allowing for the collection and analysis of the radioactivity incorporated into the aphid body, expired as COz, and rejected in the honeydew and exuviae. This method wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
71
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 50 publications
5
71
0
1
Order By: Relevance
“…It is reasonable to conclude that aphids are unable to synthesize oxylipins and take them up from the plant on which they are reared even if they contain the potential substrate to synthesize them (fatty acid profile corresponding to oxylipin profile with mainly C18:2 derivatives). Nevertheless, it is well known that artificial diets considerably perturb aphid metabolism (Febvay et al 1995) and could modify the synthesis of oxylipins for example by lack of substrate. The incubation of a crude aphid extract with radiolabeled substrate ( 14 C C18:2) revealed that the substrate is unchanged at the end of the reaction period and that no radioactivity can be detected at the retention times corresponding to the potential reaction products (HPOD and HOD).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is reasonable to conclude that aphids are unable to synthesize oxylipins and take them up from the plant on which they are reared even if they contain the potential substrate to synthesize them (fatty acid profile corresponding to oxylipin profile with mainly C18:2 derivatives). Nevertheless, it is well known that artificial diets considerably perturb aphid metabolism (Febvay et al 1995) and could modify the synthesis of oxylipins for example by lack of substrate. The incubation of a crude aphid extract with radiolabeled substrate ( 14 C C18:2) revealed that the substrate is unchanged at the end of the reaction period and that no radioactivity can be detected at the retention times corresponding to the potential reaction products (HPOD and HOD).…”
Section: Discussionmentioning
confidence: 99%
“…Aphids were collected after 10 days by brushing them carefully from the leaves into liquid nitrogen before storage at (808C. Aphids were also reared on artificial diets during 10 days before storage at (808C (Febvay et al 1995). The diet contains 10 vitamins (amino benzoic acid, ascorbic acid, biotine, calcium chloride, choline chloride, folic acid, myo-inositol, nicotinic acid, pyroxidine and thiamine), 22 amino acids (alanine, b-alanine, arginine, asparagine, aspartic acid, cystein, glutamic acid, glutamine, glycine, histidine, isoleucine, leucine, lysine, methionine, ornithine, phenylalanine, proline, serine, threonine, tryptophan, tyrosine and valine) …”
Section: Insects and Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic and physiological research reveals that Buchnera synthesizes essential amino acids for its host (6,7,(9)(10)(11)(12)). Buchnera's genome includes genes for almost all enzymes in the essential amino acid pathways and for enzymes in pathways for the nonessential amino acids tyrosine, glycine, and cysteine (6).…”
mentioning
confidence: 99%
“…aphidicola is thought to substantially contribute to the ability of aphids to thrive on plant sap, a diet of unbalanced composition that is notably poor in nitrogenous compounds (15,18,31,54). Various specific nutritional roles have been proposed, but there is strong experimental evidence only for bacterial supply of essential amino acids to the aphid (16,20,21,58). Tryptophan biosynthesis and provisioning have been studied in most detail and have rendered a coherent body of physiological, metabolic, and molecular genetic data.…”
mentioning
confidence: 99%